VD_FINDINFO Jug / 2009 / 62 vom 14. Dezember 2009 - VD Tribunal cantonal (2009)
PRÉVOYANCE PROFESSIONNELLE, COMPENSATION DU RENCHÉRISSEMENT | 144k LCP, 144r LCP, 34 LCP, 92a LCP, 36 al. 2 LPP, 44 OPP2